Rancang Bangun Rangka dan Pipa Pemanas Pada Mesin Pengering Padi - Rizky Dwi Saputro; Bayu Aji Girawan; Joko Setia Pribadi; Fadillah; Mardiyana (Politeknik Negeri Cilacap, 2021)
The climate change in Indonesia results in disruption of the rice drying process which only relies on sunlight for the drying process of rice grains so that during the rainy season farmers having problems on the process of drying rice grains. Thus, a new technology is needed in the process of drying rice grains. This technology is using a rice dryer. In the process of making a rice drying machine, there are several important components that must be designed properly, namely the frame and heating pipes which are the main components of a rice drying machine. The aim of this research was to design the frame and heating pipe for rice drying machines. From the design process, the testing phase is carried out, both machine testing and rice drying testing. The test results show that all machine components run well and the drying results show that the rice has decreased in weight after being put into the rice dryer with decrease is 5 kg to 4,9 kg or about 0,1%.